(untitled) (Analysis in Theory and Applications, 2012)
In the present paper we consider quartic piecewise polynomial for approximation to the function f ∈ C^2[0,1]. A convex type condition has been imposed in the partition so that the matrix involved for the computation of pp functions is of lower band. This reduces the computation for constructions of the pp functions for the approximation.